Evolutionary computation in combinatorial optimization : 20th European Conference, EvoCOP 2020, held as part of EvoStar 2020, Seville, Spain, April 15-17, 2020, Proceedings /: 20th European Conference, EvoCOP 2020, held as part of EvoStar 2020, Seville, Spain, April 15-17, 2020, Proceedings. (2020) - Unknown
No abstract available